Comparison of Wallgraft and Wallstent for treatment of complex iliac artery stenosis and occlusion. Preliminary results of a prospective randomized study. - Krajcer, Z (1997)
We performed a prospective randomized study to compare the use of a bare metal stent (WALLSTENT Endoprosthesis) with use of a covered stent (WALLGRAFT Endoprosthesis)-both made by Schneider, Inc.; Minneapolis, Minn-for the treatment of complex iliac artery stenosis and occlusion. We report the preliminary results of a study performed at our institution from 1 February 1997 through 31 April 1997. The patient group was composed of 6 women and 4 men, with a mean age of 61.8 years (range, 47 to 73 years). Six WALLGRAFT endoprostheses (4 in the left iliac artery and 2 in the right) and 9 WALLSTENT endoprostheses (5 in the left iliac artery and 4 in the right) were implanted. The mean percent stenosis before treatment was similar in both groups (84.17% in the WALLGRAFT group and 82.14% in the WALLSTENT group). The post-treatment stenosis and peak systolic gradients were negligible or zero in both groups. The devices were safely deployed and technical success (< 30% residual stenosis) was achieved in both groups. The mean thigh-brachial index was similar in the 2 groups, both before treatment (0.65 in the WALLGRAFT group and 0.64 in the WALLSTENT group) and after treatment (1.12 in the WALLGRAFT group and 1.12 in the WALLSTENT group). Evaluation of clinical success revealed that symptoms of intermittent claudication improved markedly in 4 of 5 patients who received the WALLGRAFT Endoprosthesis. In the WALLSTENT group, 1 patient had symptomatic improvement, another had 1 limb improve and the other worsen, and the rest had no improvement. Clinical complications were observed in only 1 patient in the WALLGRAFT group and in 2 patients in the WALLSTENT group. These preliminary results indicate very good technical and early success at the 1-month follow-up with the use of the WALLGRAFT Endoprosthesis in complex iliac artery stenosis and occlusion. Despite these promising preliminary results, a longer follow-up study with a larger number of patients is needed to determine the benefits of the WALLGRAFT Endoprosthesis in patients with complex iliac artery stenosis or occlusion.